1972
DOI: 10.1037/h0033464
|View full text |Cite
|
Sign up to set email alerts
|

Sequential effects of serial reaction time.

Abstract: The serial reaction time data from an experiment producing a negative recency effect at different interstimulus intervals were subjected to an analysis which included an investigation of up to and including fifth-order sequential effects. Third-, fourth-, and fifth-order effects were found to occur, indicating that the negative recency could not be explained by considering sequences of two events only. The implications of these findings are discussed with respect to models seeking to explain sequential effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
1
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 7 publications
8
43
1
1
Order By: Relevance
“…Second are the "alternation effects"-faster responding occurs with changing stimuli. These occur with intertrial intervals longer than 500 msec (e.g., Kirby, 1972;Moss, Engel, & Faberman, 1967). Although our finding may appear to contradict the results of these studies (we found a repetition effect with an intertrial interval that was significantly longer than 500 msec), we would like to point out that we have dissociated color, position, and shape/response, whereas these variables were confounded in the previously mentioned studies .…”
Section: Related Literature On Sequential Trial Interactionscontrasting
confidence: 56%
See 1 more Smart Citation
“…Second are the "alternation effects"-faster responding occurs with changing stimuli. These occur with intertrial intervals longer than 500 msec (e.g., Kirby, 1972;Moss, Engel, & Faberman, 1967). Although our finding may appear to contradict the results of these studies (we found a repetition effect with an intertrial interval that was significantly longer than 500 msec), we would like to point out that we have dissociated color, position, and shape/response, whereas these variables were confounded in the previously mentioned studies .…”
Section: Related Literature On Sequential Trial Interactionscontrasting
confidence: 56%
“…Priming may also account for the data obtained in two-choice reaction time paradigms (e.g., Geller, Whitman, Wrenn, & Shipley, 1971;Kirby, 1972;Remington, 1969;Schvaneveldt & Chase, 1969; see also Kowler, Martins, & Pavel, 1984), which show an orderly treelike arrangement. In these paradigms, each repetition of the stimulus produces a faster response, and alternation produces a slower response (indeed, our data produced the same kind of an orderly "tree" for the attentionfocusing feature when we analyzed all possible fifthorder sequences).…”
Section: Related Literature On Sequential Trial Interactionsmentioning
confidence: 99%
“…While in most affect the RT, and thus iK^count for the effects of of the previous research, the effect of only the stimulus sequence on RT. Laming's model emimmediately preceding stimulus (second-order ef-phasizes the subject's appraisal of the relative firefects) was analyzed, a few investigators have re-quency of the stimuli themselves as well as the ported the same trends for higher-order sequences, relative frequency of stimulus alternations and repthrough fifth-order (Kirby, 1972(Kirby, ,1976Remington, etitions. The model presented by K. Squires et al 1969Squires et al , 1971.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a cost-benefit type of negative correlation should occur between stimulus/response repetition RTs and stimulus/response alternation RTs for the current trial, depending on the preceding patterns of repetition-alternation (e.g., Audley, 1973;Kirby, 1972;Soetens, 1998;Soetens et al, 1985;. Mathematically, the strength of expectancy effects (the negative slope of the regression line) can vary orthogonally to the strength of first-order priming effects (the center of gravity of the correlation pattern being shifted toward faster repetition RT and slower alternation RT).…”
Section: Sequential Priming Effectsmentioning
confidence: 99%